2006
DOI: 10.1096/fj.06-6252fje
|View full text |Cite
|
Sign up to set email alerts
|

3'phosphoinositide‐dependent kinase‐1 is essential for ischemic preconditioning of the myocardium

Abstract: Brief periods of ischemia and reperfusion that precede sustained ischemia lead to a reduction in myocardial infarct size. This phenomenon, known as ischemic preconditioning, is mediated by signaling pathway(s) that are yet to be fully defined. 3′-phosphoinositide-dependent kinase-1 (PDK1) has been implicated in numerous cellular processes. However, the involvement of PDK1 in preconditioning has yet to be elucidated. Studying PDK1 is not as straightforward as it is for the majority of kinases, due to the lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 47 publications
2
33
0
1
Order By: Relevance
“…PDK1 (3Ј-phosphoinositide-dependent kinase-1) is activated downstream of PI3K and is the upstream regulator of Akt 16,17 and p70 ribosomal S6 kinase (p70S6K). 18 Phosphorylated levels of PDK1 (Ser241) were significantly depressed following I-R in WT hearts, while being moderately but significantly restored when hearts were subjected first to IPC before I-R ( Figure 3A). Akt possesses 2 key phosphorylated residues (Thr308 and Ser473), which are required to induce maximal activity.…”
Section: Cell-signaling Pathways In Ipcmentioning
confidence: 97%
“…PDK1 (3Ј-phosphoinositide-dependent kinase-1) is activated downstream of PI3K and is the upstream regulator of Akt 16,17 and p70 ribosomal S6 kinase (p70S6K). 18 Phosphorylated levels of PDK1 (Ser241) were significantly depressed following I-R in WT hearts, while being moderately but significantly restored when hearts were subjected first to IPC before I-R ( Figure 3A). Akt possesses 2 key phosphorylated residues (Thr308 and Ser473), which are required to induce maximal activity.…”
Section: Cell-signaling Pathways In Ipcmentioning
confidence: 97%
“…Interestingly, PDK1-MCKCre mice showed attenuation of cardimyocyte cell growth and impairment of left ventricular (LV) contraction. It was reported that cardiomyocytes deficient for Pdk1 were sensitive to hypoxia (5), and that ischemic preconditioning failed to protect Pdk1-hypomorphic mutant mice against myocardial infarction (MI) (6). However, the mechanisms of how PDK1 deficiency induces these cardiac abnormalities remain to be resolved.…”
mentioning
confidence: 99%
“…K ATP channels are opened in a cGMP-dependent manner (Oldenburg et al, 2002(Oldenburg et al, , 2004Qin et al, 2004). Activation of sarcolemmal K ATP channels shortens action membrane potential duration and decreases intracellular Ca 2ϩ loading (Budas et al, 2004(Budas et al, , 2006, and mito-K ATP channel opening attenuates mitochondrial calcium accumulation, prevents Ca 2ϩ -promoted oxidative stress, maintains mitochondrial membrane integrity, and inhibits opening of the mPTP (Facundo et al, 2005). Therefore, PI3K/ Akt signaling may recruit multiple cardioprotective pathways to reduce myocardial damage after ischemia and reperfusion.…”
Section: Discussionmentioning
confidence: 99%